Transformasi Komunikasi Dakwah Perspektif Filsafat Ilmu di Era Digital - Junaidi; Mulyadi Erman; Edy Musoffa (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The substance of Islamic da'wah is a fundamental activity that must be continually actualized to meet the need for information and religious education in the digital era, which is highly susceptible to a paradigm of spiritual drought, moral and value decadence, and behavioral and cultural changes that can deviate from Islamic doctrinal values. This study aims to describe da'wah communication in the digital era as a philosophical foundation for the philosophy of science for contemporary society. Digital communication in da'wah can serve as a role model and pattern for instilling values, fostering character, and promoting exemplary behavior on social media. The method used in this study is a descriptive qualitative method, with data collection techniques including literature reviews and content analysis. Data analysis is systematically conducted using academic, scientific, and qualitative methods. The novelty and urgency of this research lie in its attempt to build an integrative da'wah philosophical paradigm as a new conceptual synthesis in da'wah scientific studies. The research gap that emerged is the absence of a comprehensive, integrated framework for da'wah philosophical science that explains its position, methods, and objectives as an independent science. Therefore, this research offers a new conceptual paradigm, namely the philosophy of integrative da'wah science, which places monotheism as the unifying principle between the essence, method, and value of da'wah. This paradigm not only strengthens the existence of da'wah as a complete and independent Islamic scientific discipline but also provides a new direction for the development of da'wah theory and practice that is scientific, contextual, and oriented towards social and spiritual transformation in the modern era.